Gold catalysis: AuCl-induced polymerization of styrene and n-butylvinylether - Hashmi, A. Stephen K.; Schäfer, Sascha; Göker, Verena; Eisenbach, Claus D.; Dirnberger, Klaus; Zhao-Karger, Zhirong; Crewdson, Patrick (Australian journal of chemistry, 2014)
Polymerization of styrene, 4-methoxystyrene, and n-butylvinylether was achieved using simple AuCl as catalyst and AgPF6 as cocatalyst. High molecular weights and low polydispersity indices were obtained. Evidence for a cationic mechanism was obtained by reactions with nucleophiles. The mechanistic study also indicates a living polymerization with the gold(i)-alkene complex as the resting species.
Gesehen am 30.10.2020